The incorporation of elder people to the grandparent's home of the community - Danay Martínez-Revé; Leonardo Borrero-González (Universidad de Guantánamo, 2011)
In this paper´s content it is reflected the rationale underpinning physical activity in older adults, to promote physical and spiritual wellbeing of this group. By the diagnose, it was corroborated poor incorporation to recreation and the grandparents home´s activities given the poor support of the Municipal Institute of Sports in Torres (IMDETOR) and the disregard for their likes and preferences which constitutes an obstacle to planning activities that meet their expectations and are beneficial to improve health and enhance inclusion in the circle of grandparents. The strategy can enhance the incorporation of elders and the understanding of the importance of improving their physical and mental qualities.